A Case of Recalcitrant Circinate Generalized (Lapière) Psoriasis Successfully Treated with Risankizumab - Angelo Ruggiero; Wanda Lauro; Gabriella Fabbrocini; Chiara Miano; Alessia Villani; Claudio Marasca (Karger Publishers, 2022)
Circinate (Lapière) psoriasis represents a rare variety of generalized subacute pustular psoriasis clinically characterized by rapid onset of annular circinate lesions with micro-pustules at the borders without classic plaque psoriasis manifestations. Most reported cases have been described in childhood with a relative benign course, fast and long-term remission after treatment. However, the recalcitrant course may result in an important negative impact on patients' quality of life. Many systemic treatments have been reported for the management of moderate to severe forms, with variable clinical outcomes. However, data about the use of biologics in this rare psoriasis subtype are still lacking. Herein, we report the first case of circinate psoriasis unresponsive to methotrexate and almost all classes of biologics approved for psoriasis (anti-tumour necrosis factor (TNF), anti-interleukin (IL)-12/23, and anti-IL-17) which was successfully treated with risankizumab (anti-IL-23).